RANCANG BANGUN SISTEM PENDETEKSI KEBAKARAN DAN PEMADAM API OTOMATIS BERBASIS INTERNET OF THINGS (IoT) - Anggarani, Agustina; Muqorobin Muqorobin; Feri Efendi, Tino (Jurnal Riset Teknik Komputer, 2024)
Fire is an event caused by an uncontrolled ignition source, which generally occurs due to human negligence when using electronic devices without being careful which can cause electrical short circuits and fires. Firefighters often have difficulty extinguishing fires, due to late early detection information regarding fires, so that handling is delayed. Because of this phenomenon, a system is needed that can help prevent fires. This research aims to produce an IoT-based automatic fire detection and fire extinguishing system, as well as to measure and evaluate the system's level of accuracy in detecting fires and responding by extinguishing them. This research will explain the design process for an IoT-based automatic fire detection and extinguishing system, using the System Development Life Cycle Waterfall model research method. The final result of this research is that the author succeeded in creating an Internet of Things (IoT)-based Automatic Fire Detection and Fire Extinguishing System, which is systematically able to detect the presence of fire and gas and perform automatic fire extinguishing functions, and users can also receive notifications via WhatsApp. The author also succeeded in measuring the level of accuracy of the IoT-based automatic fire detection and extinguishing system.